Penanaman Nilai-nilai Nasionalis pada Warga Belajar Kejar Paket C Kota Tangerang Selatan Banten - Darmawan, Dadan; Rawita, Ino Sutisno (Journal of Nonformal Education and Community Empowerment, 2020)
This study aims to reveal the strengthening of character education through habituation activities in cultivating nationalist values in PKBM Bina Mandiri. The research method uses qualitative. The research subjects are the founders of the institute, tutors and learning citizens. Data collection techniques using interviews, observation and documentation. Data analysis used triangulation of sources and methods. The results of the study revealed that the application of a nationalist feeling to learning citizens was focused on habituation activities. PKBM already has its own uniform with a batik motif which is a characteristic of the Indonesian state. Always commemorating national holidays by holding various types of competitions that show his love for the country. Besides that, the love of the country has also been shown through the spirit of nationalism by continuing to want to continue education, and always implementing a clean and healthy life.